Dietary supplementation of Polygonum chinense improves the immunity of Asian seabass, Lates calcarifer (Bloch, 1790) against Vibrio harveyi infection - Abdul Razak, Rashidah; Shariff, Mohamed; Md. Yusoff, Fatimah; Ismail, Intan Safinar (Elsevier Ltd, 2023)
Aquaculture plays a significant role in the overall fish production in Malaysia, contributing a substantial quantity of food-fish amounting to roughly 573,683 tonnes with an estimated economic value of US$860 million in 2022. However, diseases have become a significant limitation for aquaculture production. Therefore, herbal immu-nostimulant has been considered a natural and practical approach of preventing disease infection in fish. The ability of Polygonum chinense extract (PCE) on haemato-biochemistry parameters, immunomodulatory properties, and disease resistance of Lates calcarifer (Asian seabass) under Vibrio harveyi challenge was evaluated in this study, with a focus on dose-response associations and variability over various exposure durations (0-, 7- and 14- day post-infection). A total of 480 Asian seabass (9.5 ± 0.2 g) were distributed in 12 aquaria and fed four diets supplemented with 0 (control), 2, 5 and 10 g/kg diet for 60 days before being challenged with V. harveyi. Dietary PCE significantly improved (P < 0.05) survival, with the dose of 10 g/kg showing the highest survival rate (90 %) when compared to the control (60 %). Additionally, hematological (red and white blood cell counts, hemoglo- bulin, packed cell volume, and mean corpuscular volume) and immunological (activities of lysozyme, phagocytic activity and respiratory burst, and serum total immunoglobulin) properties were significantly increased (P <0.05) in comparison to the control group. In contrast, serum aspartate aminotransferase and alanine amino-transferase levels, as well as glucose level were significantly reduced (P < 0.05) in PCE-fed fish compared to the control group. Conclusively, the current study discovered that supplementing fish feed with P. chinense extract improves fish haemato-biochemical profile, immunocompetence and disease resistance to V. harveyi infection.